2021
DOI: 10.1177/07356331211062925
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects in the Effectiveness of Educational Virtual Field Trips

Abstract: Virtual and immersive virtual reality, VR and iVR, provide flexible and engaging learning opportunities, such as virtual field trips (VFTs). Despite its growing popularity for education, understanding how iVR compared to non-immersive media influences learning is still challenged by mixed empirical results and a lack of longitudinal research. This study addresses these issues through an experiment in which undergraduate geoscience students attended two temporally separated VFT sessions through desktop virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Virtual reality can teleport users to various places, and it facilitates a sense of presence. Therefore, the popularity of virtual trips and expeditions and their positive longitudinal effects on learning have been growing (eg, Makransky & Mayer, 2022; Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality can teleport users to various places, and it facilitates a sense of presence. Therefore, the popularity of virtual trips and expeditions and their positive longitudinal effects on learning have been growing (eg, Makransky & Mayer, 2022; Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This affective state could also explain why they were more engaged and involved since they can navigate the real world even in the comfort of their homes as compared to simply watching static videos. Although pupils may have been overwhelmed by the novelty effect of a VFT as mentioned in other studies (e.g., Zhao et al, 2021 ), the longitudinal nature of our experiment settles this uncertainty. Upon examination, these positive affective outcomes seem to be in a tug of war with the cognitive outcomes.…”
Section: Discussionmentioning
confidence: 56%
“…Virtual field trips allow students and teachers to explore once inaccessible settings without additional time, expertise, and expense. Research behind virtual field trips is in its infancy, yet initial findings are positive (Zhao et al, 2022). In Zhao and Colleagues study, (2022) they found head-mounted display and mobile device VR field trips had positive effects on student learning, engagement, motivation, and enjoyment.…”
Section: Delivering Hands-on Learning Through Vr Technologymentioning
confidence: 99%